2016
DOI: 10.1017/s0007114516001926
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Alternative Healthy Eating Index in relation to depression and anxiety in Iranian adults

Abstract: Earlier studies have shown a protective association between adherence to healthy eating guidelines and mental disorders in Western nations; however, data in this regard are limited from the understudied region of Middle East. We examined the association between adherence to healthy eating guidelines, as measured by Alternative Healthy Eating Index (AHEI)-2010, and prevalence of anxiety and depression in a large sample of Iranian adults. In this cross-sectional study, data on dietary intakes of 3363 adult parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 34 publications
2
44
3
2
Order By: Relevance
“…We found a significant inverse association between adherence to the mPNNS-GS, the PANDiet and the DQI-I and the risk of depressive symptoms. Regarding the AHEI-2010, which has been extensively used in the scientific literature, we found a non-significant association, in contrast to other published studies (15,19,24) . In the Seguimiento Universidad de Navarra Cohort study including 15 093 participants, adherence to the AHEI-2010 at baseline was inversely associated with depression risk (HR quintile 5 compared with quintile 1: 0•72; 95 % CI 0•59, 0•88) (15) .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found a significant inverse association between adherence to the mPNNS-GS, the PANDiet and the DQI-I and the risk of depressive symptoms. Regarding the AHEI-2010, which has been extensively used in the scientific literature, we found a non-significant association, in contrast to other published studies (15,19,24) . In the Seguimiento Universidad de Navarra Cohort study including 15 093 participants, adherence to the AHEI-2010 at baseline was inversely associated with depression risk (HR quintile 5 compared with quintile 1: 0•72; 95 % CI 0•59, 0•88) (15) .…”
Section: Discussioncontrasting
confidence: 99%
“…In the Seguimiento Universidad de Navarra Cohort study including 15 093 participants, adherence to the AHEI-2010 at baseline was inversely associated with depression risk (HR quintile 5 compared with quintile 1: 0•72; 95 % CI 0•59, 0•88) (15) . In the cross-sectional studies published by Saneei et al including 3363 Iranian adults with a mean age of 36•3 (SD 7•9) years, adherence to the AHEI-2010 was also significantly inversely associated with depression risk (19,24) . In addition, a study based on the Whitehall II cohort including 4215 participants aged 35-55 years at baseline reported a significant inverse association between high adherence to the AHEI and recurrent depressive symptoms only among women (OR for a 1-SD increase: 0•59; 95 % CI 0•47, 0•75) (27) .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Compared to the intake of single nutrients or foods, considering the general pattern of diet to assess diet quality could provide a better insight into diet-disease relations and may be more predictive of chronic disease risk (15). In this context, several studies have investigated the association between diet quality and psychiatric disorders (16,17). Dietary diversity score (DDS), as an indicator of diversity within food groups, is a reliable diet quality index (18).…”
Section: Introductionmentioning
confidence: 99%
“…A study on 1118 African-American residents of Baltimore, USA, demonstrated an inverse association between adherence to the HEI-2010 and depression 14. Another study reported a 49% and 45% reduced chance for anxiety and depression among subjects adhering to the Alternative Healthy Eating Index (AHEI-2010) 15. Other studies have also inversely linked adherence to a healthy diet with psychological disorders 16.…”
Section: Introductionmentioning
confidence: 99%